Analysis of the Role of the Student Cooperative Communication Forum of the First Sumatra Region (FKKMI SUMBAGTAMA) in Strengthening Collaboration among Student Cooperatives in the Sumatra Region - Indah Kusuma Wati; Karinda Gayatri; Ritta Ardiati; Dian Dwi Wijaksana; Aminah Ramalia (J-Coop : Journal of Co-operative, 2026)
This study aims to analyze the role of the Forum Komunikasi Koperasi Mahasiswa Indonesia (FKKMI) Sumbagtama in strengthening collaboration among student cooperatives in the Sumatra Bagian Pertama region. The research employed a qualitative approach with a descriptive method. Data were collected through structured interviews with the Chairperson of FKKMI Sumbagtama as the main informant and supported by organizational membership data. The results showed that FKKMI Sumbagtama plays an important role as a communication and coordination forum for student cooperatives from various universities in several provinces, including Jambi, Aceh, North Sumatra, West Sumatra, Riau Islands, Bengkulu, and Riau. Organizational communication is carried out through discussion forums, coordination meetings, and digital communication media aimed at maintaining active and well-directed relationships among organization members. In addition, organizational activities such as the National Conference (MUNAS), Regional Conference (MUSWIL), and Regional Working Meeting (RAKERWIL) serve as important platforms for strengthening coordination, formulating work programs, and increasing member participation within the organization. The findings also indicate that FKKMI Sumbagtama contributes to the development of student cooperative organizations by improving communication skills, leadership, and organizational cooperation among members. Therefore, FKKMI Sumbagtama functions not only as a formal communication forum but also as a means of strengthening institutional relationships and developing student cooperatives in the Sumatra Bagian Pertama region. Keywords: FKKMI Sumbagtama, student cooperatives, organizational communication, organizational coordination, organizational collaboration.